PEMBUATAN SISTEM PENENTUAN KOEFISIEN GESEK STATIS BENDA PADA BIDANG MIRING SECARA DIGITAL BERBASIS MIKROKONTROLER - Fitri, Maisa; Hufri, Hufri; Yohandri, Yohandri (Sainstek : Jurnal Sains dan Teknologi, 2014)
The purpose of this research was to design a system of determination of the static friction coefficient of the object on inclined plane digitally. The purpose of this research is to explain the performance specifications, accuracy and precision of the system. There were three main results of this research. Firstly, the system was designed with the surface of the slip object size 8,7 x15 cm and glide plane 9 x 100 cm. Secondly, the average of accuracy relative accelerometer sensor was 95,58%. Thirdly, average precision was 0,977.Keywords: Static friction coefficient, accelerometer, tilt sensor